PELATIHAN DIVERSIFIKASI OLAHAN TEMPE PADA PENGRAJIN TEMPE DI DESA PAREREJO KECAMATAN PURWODADI KABUPATEN PASURUSAN - Anugerah Dany Priyanto; Sri Djajati; Jariyah (Universitas Nahdlatul Ulama Sidoarjo, 2018)
One of the tempeh craftsmen villages is Parerejo, Purwodadi Subdistrict, Pasuruan Regency. A total of 107 work and depend on their income as tempeh producers in that area. Thus far, most of the craftsmen only sold it in the form of fresh tempeh. Only view people are using tempeh as tempeh chips. Consequenetly, the tempeh are not sold on a day that is wasted due to the shelf life is not long enough. The introducing of implementers was carried out slowly and kinship before the main program was carried out. This program used fresh tempeh which was adjusted to the implementation of food technology knowledge. This was conducted by processing fresh tempeh into three types of diversified tempeh products such as mendoan tempeh, tempeh balls, and tempeh rolade. In this service program, communicative language was used to accompany knowledge transfer about tempeh processing to the tempe craftsmen community. This program was conducted to intend that the given information can be accepted by the community, so that this community service program get a positive response. After conducting counseling and training to the tempeh craftsmen community, some of enthusiastic were got from craftsmen when they did the activities. Most of the craftsmen did not yet know the diversification of processed tempeh products that were delivered by the team. As a result of this service program, it can be concluded that these activities were very beneficial for the tempeh craftsmen community in Parerejo Village and they hope that the service activities with more various materials.